1997
DOI: 10.2165/00003088-199733010-00005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Fluconazole in Superficial and Systemic Mycoses

Abstract: The bis triazole agent fluconazole is used widely in the treatment of superficial and deep mycoses. A single oral dose of fluconazole 150 mg gives a mean long term clinical cure rate of 84 +/- 5% and is considered a valuable alternative to other topical antifungal drugs for vaginal candidiasis. A clinical cure rate of 90.4% for oropharyngeal candidiasis was obtained with 100mg daily for a minimum of 14 days; however, as for the other azoles the rate of relapse was large (40%) in immunocompromised patients. A d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
6

Year Published

1999
1999
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(93 citation statements)
references
References 156 publications
4
83
0
6
Order By: Relevance
“…The mean population pharmacokinetic parameter estimates were in the same range as those already reported [14,15,16,17]. Although a previous study reported no e ect of BW on¯uconazole pharmacokinetics [16], in this study BW signi®cantly in¯uenced¯uconaz-ole CL and V d .…”
Section: Discussionsupporting
confidence: 83%
“…The mean population pharmacokinetic parameter estimates were in the same range as those already reported [14,15,16,17]. Although a previous study reported no e ect of BW on¯uconazole pharmacokinetics [16], in this study BW signi®cantly in¯uenced¯uconaz-ole CL and V d .…”
Section: Discussionsupporting
confidence: 83%
“…Acinetobacter baumannii meningitis has been treated successfully with 2 g ampicillin plus 1 g sulbactam every 3 h without severe adverse drug effects (33). The daily dose of fluconazole can be increased up to 1,600 mg with tolerable side effects (44,58).…”
Section: Methods To Increase Drug Concentrations In Central Nervous Smentioning
confidence: 99%
“…Neonates require approximately 5 days to reach steady-state [59], and maintenance fluconazole doses of 12 mg/kg/day are necessary to achieve exposures similar to older children and adults [60]. Thus, a loading dose of 25 mg/kg to achieve steady state concentrations sooner than the traditional dosing scheme may be appropriate.…”
Section: Pharmacokinetics In Childrenmentioning
confidence: 99%